Electric Vehicles, Tax incentives and Emissions : Evidence from Norway - Camara, Youssouf; Holtsmark, Bjart; Misch, Florian (Washington, D.C. : International Monetary Fund, 2021)
This paper empirically estimates the effects of electric vehicles (EVs) on passenger car emissions to inform the design of policies that encourage EV purchases in Norway. We use exceptionally rich data on the universe of cars and households from Norway, which has a very high share of EVs, thanks to generous tax incentives and other policies. Our estimates suggest that household-level emission savings from the purchase of additional EVs are limited, resulting in high implicit abatement costs of Norway's tax incentives relative to emission savings. However, the estimated emission savings are much larger if EVs replace the dirtiest cars. Norway's experience may also help inform similar policies in other countries as they ramp up their own national climate mitigation strategies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Factor Income Distribution; Foreign Exchange; Informal Economy; Taxation, Subsidies, and Revenue; Underground Econom